2014
DOI: 10.5586/asbp.2000.024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extract from shoots of Taxus baccata var. 'Elegantissima' on mitotic activity of meristematic cells of Allium cepa L. roots

Abstract: We investigated the influence of different concentrations of alcoholic extract from young shoots of Taxus baccata var. 'Elegantissima' (TbE), containing paclitaxel (81.6 µg/g fresh mass), on mitotic activity and DNA content in meristematic ` cells of Allium cepn adventitious root tips. During 24 hours of incubation we obtained different level of inhibition of mitotic activity: ranging from slight changes (dilution 1:32), through complete inhibition reversible in postincubation (dilution 1:8),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…The growth interference of B. decumbens in the presence of volatile oils is associated with interferences in the process of cell division, by means of partial blocking of subsequent phases of division at higher concentrations, which may be associated with changes in the structure of chromosomes in prophase and metaphase, as well as disturbances in prophase and anaphase. Similar changes were observed in A. cepa cell chromatids submitted to a Taxus baccata aqueous extract (Majewska et al, 2000).…”
Section: (C) (D) (A) (B) (%) (%) (%) (%)supporting
confidence: 79%
“…The growth interference of B. decumbens in the presence of volatile oils is associated with interferences in the process of cell division, by means of partial blocking of subsequent phases of division at higher concentrations, which may be associated with changes in the structure of chromosomes in prophase and metaphase, as well as disturbances in prophase and anaphase. Similar changes were observed in A. cepa cell chromatids submitted to a Taxus baccata aqueous extract (Majewska et al, 2000).…”
Section: (C) (D) (A) (B) (%) (%) (%) (%)supporting
confidence: 79%
“…Esse fato pode ser atribuído à capacidade dos compostos presentes na FAE em reduzir o índice mitótico, bloqueando parcialmente as fases subsequentes da divisão celular nas maiores concentrações. Mudanças semelhantes Ciência Rural, v.43, n.4, abr, 2013. foram observadas nas cromátides das células de A. cepa, submetidas ao extrato aquoso de Taxus baccata (MAJEWSKA et al, 2000). Essa interferência na divisão celular causada pela ação das substâncias químicas contidas na FAEC com acentuado efeito sobre a morfologia do sistema radicular provavelmente representa um dos mecanismos de ação das substâncias (s) com atividade fi totóxica.…”
Section: Resultsunclassified
“…Using this strategy, Sánchez-Moreiras et al (2008) found that benzoxazolin-2(3H)-one, an allelopathic compound produced by Secale cereale, retarded the cell cycle in L. sativa root meristems by blocking the G 2 /M checkpoint. Similar effects on A. cepa root tips were induced by extracts of the medicinal plants Rhodiola rosea, Taxus baccata, and T. brevifolia (Majewska et al, 2000(Majewska et al, , 2003(Majewska et al, , 2008. Roots of A. cepa were also used to determine the mode of action of cyanamide, an allelochemical produced by Vicia villosa (Soltys et al, 2011).…”
Section: Effect Of Cytotoxic Compounds/elementsmentioning
confidence: 87%